Advances in 3D Materials‐Based Hydrovoltaic Generators and Synergistic Energy Conversion - Kai Jiao; Boxuan Ma; Xinxi Liu; Bohao Chen; Qiuwang Wang; Cunlu Zhao (ChemElectroChem, 2024)
Abstract Covering approximately 71 % of Earth's surface and absorbing almost 70 % of the solar radiation energy, water presents a tremendous opportunity for hydropower generation, revealing considerable promise for future applications. Benefited from the low cost, negligible pollution, and the characteristic of solely utilizing ambient thermal energy, hydrovoltaic (HV) technology has garnered significant attention in recent years for its substantial contributions to energy harvesting and conversion. While traditional hydrovoltaic generators (HVGs) have predominantly utilized two‐dimensional (2D) structures, the emergence of three‐dimensional (3D) HV materials signifies a pivotal shift due to superior specific surface areas, intricate porous architectures and enhanced mechanical strength. Herein, we summarized the development of 3D HVGs, categorizing them into flow‐induced, moisture‐induced, and evaporation‐induced types. We explored their working mechanisms, evolutions, strategies for electricity output enhancement and the limitations they face. Moreover, we discussed the integration of HVGs with other energy conversion technologies and the development of comprehensive HVG systems that exploit various water sources for energy generation. At last, we highlighted the challenges confronting 3D HVGs and anticipated future directions for this burgeoning field.